Evaluasi Kinerja Tenaga Penyadap Karet (Hevea brasiliensis Muell. Arg.) Berdasarkan Kualitas Sadap - Herlinda, Fadila; Tahir, Muhammad; Delvitasari, Febrina; Riniarti, Dewi (Politeknik Negeri Lampung, 2022)
The performance of tappers has an effect on the high or low level of production and productivity of the latex produced by a company. However, many tappers are only fixated on the production target (quantity) that must be achieved rather than paying attention to the quality of the tapping. This study aims to analyze the performance of tappers based on the quality of tapping and the factors that influence it and to determine the application of the premium system. The research was conducted from November to December 2019 at PT Perkebunan Nusantara VII Way Berulu, Pesawaran, Lampung. The research used a survey method and purposive sampling technique by selecting 12 tappers based on age, education level, and work experience and observing 5 sample trees from each tapper. Data were analyzed using descriptive analysis and level test analysis of 5%. The results showed that the performance of tappers is in the good category, because it has few wood wounds and the depth of tapping and bark consumption is in accordance with recommended norms. The factors of age, education level and work experience do not have a significant effect on the performance of tappers. All tappers do not receive a premium because it does not exceed the task bases.